2016
DOI: 10.7567/jjap.55.02bc13
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of hydroxyl groups in silica glass through the binding interface

Abstract: Diffusion of hydroxyl groups in silica glass through an interface formed by binding between high-hydroxyl (ca. 1200 wt.ppm) and low-hydroxyl (ca. 130 wt.ppm)-containing silica glasses in the temperature range of 900–1150 °C was investigated. Although the theoretical curve with a hydroxyl-concentration-independent diffusion coefficient deviates from the experimental curve, the diffusion coefficients obtained by fitting to the experimental results by the least squares method coincided with the “effective diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…(2). 28) The temperature dependence of the proportionality coefficient κ between the hydroxyl concentration and the diffusion coefficient showed that the value of κ at 1150 °C was larger than that extrapolated from the data at lower temperatures. 28) We considered that this "singularity" may be correlated to the glass transition because 1150 °C is the near the glass transition point observed by light scattering.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…(2). 28) The temperature dependence of the proportionality coefficient κ between the hydroxyl concentration and the diffusion coefficient showed that the value of κ at 1150 °C was larger than that extrapolated from the data at lower temperatures. 28) We considered that this "singularity" may be correlated to the glass transition because 1150 °C is the near the glass transition point observed by light scattering.…”
Section: Introductionmentioning
confidence: 90%
“…28) The temperature dependence of the proportionality coefficient κ between the hydroxyl concentration and the diffusion coefficient showed that the value of κ at 1150 °C was larger than that extrapolated from the data at lower temperatures. 28) We considered that this "singularity" may be correlated to the glass transition because 1150 °C is the near the glass transition point observed by light scattering. 30) However, the possibility that this "singularity" only originates from the experimental error cannot be ruled out because of the insufficient numbers of temperatures and heat treatment times in the measurement to rule out this possibility.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations